Healing of fatigue delamination cracks in carbon–epoxy composite using mendable polymer stitching. (January 2014) - Pingkarawat, Khomkrit; Wang, Chun H; Varley, Russell J; Mouritz, Adrian P
This article presents an experimental investigation into the mode I delamination fatigue properties and fatigue crack healing mechanism of a self-healing carbon fibre–epoxy composite containing mendable thermoplastic stitches. Mode I interlaminar fatigue tests using double cantilever bending specimens show that through-the-thickness reinforcement of the composite with mendable poly(ethylene- co -(methacrylic acid)) stitches is highly effective in healing delamination cracks and restoring the fatigue properties. Aided by a pressure delivery mechanism unique to this type of mendable thermoplastic, the healing agent stored in an interconnected network of stitches is able to flow into narrow delamination cracks. The mode I interlaminar fatigue resistance as well as the fracture toughness of the composite was fully restored by poly(ethylene- co -(methacrylic acid)) stitches. Transverse tension tests were performed to determine the traction law of the healing agent, which controls the healing efficiency and interlaminar toughening mechanism under static and fatigue mode I interlaminar loading.